Effect of gamma irradiation on phenol content, antioxidant activity and biological activity of black maca and red maca extracts (Lepidium meyenii walp) - Zevallos-Concha, A (2016)
This study was performed to determine the effects of gamma irradiation on UV spectrum on maca, total content of polyphenols, 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical-scavenging activities and in vivo biological activities of red and black maca extracts (Lepidium meyenii).